The Influence Of Lifestyle On Revisit Intention At V Coffee Padang : Customer Satisfaction As Mediator - Muhammad Jidan; Astri Yuza Sari (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
This research investigates the lifestyle of those who intend to revisit V Coffee Shop in Padang City with customer satisfaction as a mediator. A quantitative approach was used by distributing questionnaires to 110 respondents who had visited the coffee shop.. Employing a quantitative method, data were collected through a structured questionnaire from 110 respondents who had previously visited the coffee shop. The analysis was conducted using Structural Equation Modeling with Partial Least Squares (SEM-PLS) via SmartPLS 4.0. The findings indicate that lifestyle does not have a significant influence on customer satisfaction. In contrast, customer satisfaction significantly influences revisit intention. Moreover, customer satisfaction does not mediate the relationship between lifestyle and revisit intention. These results suggest that while lifestyle may shape customer preferences, it does not directly translate into satisfaction or loyalty in this context. Customer satisfaction emerges as the most critical factor in fostering revisit intention. This study offers theoretical contributions to consumer behavior literature and practical implications for service enhancement strategies in the coffee shop industry